Engenharia de requisitos de um software educacional com a participação de adolescentes - Silveira, Cristiane Fontoura (2018)
Digital technologies are part of the daily life of different people and they are used to many purposes, including supporting teaching and learning practices. The computer provides resources to pedagogical tasks, like the educational software. Its development includes teamwork and it must consider pedagogical aspects and its target audience, the students. As well as children, through Participative Design, teenagers can contribute, as design partners, during the development process of new technologies. When accomplishing a literature review in order to find contributions to the development of educational software with teenagers participation, we verified the importance of observing pedagogical aspects and the subject in perspective, but no contributions to educational software development with teenagers were observed. Thus, this undergraduate thesis integrates the Participatory Design practices to the Requirements Engineering knowledge in an educational context with the participation of teenagers, in order to support the development of an educational software to teaching and learning Mathematics. Students from a 8th year class and the Math teacher of Arthur Hormain State Elementary School, located in Polo Rural dos Pinheiros, in the city of Alegrete/RS, participated in this study. As the result of this undergraduate thesis, we present the Requirement Specification of the game Soverte Turbo, which organizes the functional and non-functional requirements, as well as the prototypes created by the students. From the organized requirements, the game should be developed as part of the activities of the extension program GEInfoEdu – Computing in Education Studying Group.